Prevalence of Enteropathogens in Suckling and Weaned Piglets with Diarrhoea in Southern Germany - Wieler, L. H. (J Vet Med B Infect Dis Vet Public Health, 2008)
Faecal samples from suckling (n=205) and weaned piglets (n=82) with diarrhoea from 24 farms in Southern Germany were examined for shedding of important metazoic parasitic, viral and bacterial pathogens using culture, microscopic and electronmicroscopic methods. Escherichia coli isolates were tested further for the enterotoxin genes est‐Ia and elt‐I by colony blot hybridization. Isospora suis was diagnosed in 26.9 % and Cryptosporidium parvum in 1.4 % of the piglets investigated. The proportion of coronavirus‐positive animals was 13.4 % and 4 % were positive for rotavirus. It was found that 17.6 % of the animals were infected with enterotoxigenic E. coli (ETEC; 10.1 % ETEC‐ST‐Ia and 8.6 % ETEC‐LT‐I, respectively). The occurrence of the pathogens was significantly associated with the age of the animals examined (P < 0.001). Isospora suis was predominantly isolated from suckling piglets (in the second and third week of life), while in weaned piglets (fourth week of life) rotavirus and ETEC were most prevalent. On 22 of the 24 piglet production farms examined at least one of the investigated pathogens was detected. Coronavirus was diagnosed in 66.7 %, I. suis in 62.5 %, rotavirus in 20.8 % and C. parvum in 8.3 % of the farms. These results underline the fact that despite the hygienic, technical and immune preventive efforts during the last years, enteropathogens are still common in German piglet production units.